Thwarted: relinquishing educator beliefs to understand translanguaging from learners' point of view. Issue 3 (3rd July 2019) - Mendoza, Anna; Parba, Jayson
ABSTRACT: This study took place in a 300-level Filipino class at Hawai'i's state university. Originally, the researchers intended to study how English-Filipino translanguaging, the use of linguistic features of different languages to achieve meaning-making, (1) supports development of academic writing skills in Filipino for heritage learners who have undergone subtractive bilingualism and (2) challenges the ideology of discrete languages and speech communities. However, throughout the term, students' translanguaging practices did not necessarily improve their writing skills in Filipino, and interviews revealed that they still saw themselves as having varied proficiency in English, Filipino (Tagalog-based), and other Filipino languages, which they linked to particular speech communities. Nevertheless, students participated actively and felt they were learning, and translanguaging led to understanding of deeper and more critical content. From these findings, we propose a translanguaging pedagogy that recognises the different social realms in which students have various opportunities to develop different parts of their linguistic repertoires, rather than a pedagogy that simply strives to dissolve linguistic barriers to promote bilingualism and biliteracy.